Seznam katalogov in kartotek v Univerzitetni knjižnici Maribor - Sapač, Irena (Knjižnica, 1984)
The University Library Maribor has over one hundred catalogues and book lists of various form and purpose, some of which are intended for users, while many others are hidden in separate departments of the Library. Describing the most important catalogues, especially those bringing whatever data on library materials held in the University Library Maribor, the article gives information about some catalogues in the acquisition and cataloguing departments, in the lending -, reference -, documentation -, and bibliographic services division and in the special collections. A synoptic table of all the catalogues and book lists in the University Library Maribor is given at the end.
Keywords: visokošolske knjižnice; Maribor; Univerzitetna knjižnica Maribor; knjižnični katalogi; seznami